Pelatihan Digitalisasi dan Branding untuk Meningkatkan Daya Tarik Produk Olahan Jambu Air di Desa Pranan - Dhiyaa Faa’izah; Hamida, Syakila; Muhammad Irfan Satriya Dewanto; Gazel Rahmad Trivanjodi; Tiara Annisa Putri; Naura Athira Arraudha; Ghaitsa Athar Kirana; Latifa Assisi Rosyada; Supratikno (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2024)
This study aims to enhance the competitiveness and appeal of processed water guava products in Pranan Village through digitalization and branding training using hands-on supervised training. The training was designed to empower the PKK women's group with knowledge and skills in utilizing digital technology for product marketing. The program began with theoretical education on effective branding concepts, followed by hands-on practice using Canva and Capcut applications. Participants received step-by-step guidance in creating creative and engaging digital marketing media. The hands-on training was supervised to ensure that each participant could effectively apply the taught materials. The results of this training showed a significant improvement in participants' ability to understand and implement branding techniques, as well as utilizing digital tools in their marketing strategies. Additionally, feedback from participants indicated increased confidence in managing and marketing processed water guava products more professionally. The conclusion of this study is that hands-on supervised training in digitalization and branding can effectively enhance digital marketing competence and ultimately support the increased sales and competitiveness of local products. This success highlights the importance of practical and targeted training approaches in empowering local communities to adapt to the increasingly digital market demands.